2016
DOI: 10.1177/1523422316645884
|View full text |Cite
|
Sign up to set email alerts
|

Action Learning and Leadership Development

Abstract: The Problem. Today organizations worldwide are faced with the growing challenge of increasing the capabilities of their leaders with less time and fewer financial resources. However, most leadership development programs are ineffective and expensive and provide little focus on the social, interpersonal, and strategic aspects of leadership. This research seeks to answer the following questions:1. How are leadership skills developed through action learning? 2. How are these skills embodied and consequently trans… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
27
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(27 citation statements)
references
References 32 publications
0
27
0
Order By: Relevance
“…In conclusion, it is evident that over recent years organisations have turned to AL as an adaptive and effective methodology for developing their managers (Dotlich and Noel, 1998;Boshyk, 2002;O'Neil and Marsick, 2007;Boshyk and Dilworth, 2010;Volz-Peacock, Carson and Marquardt, 2016). The focus on learning while working through challenging work problems has also been clearly highlighted in the literature.…”
Section: The Role Of the Action Learning Facilitatormentioning
confidence: 97%
See 1 more Smart Citation
“…In conclusion, it is evident that over recent years organisations have turned to AL as an adaptive and effective methodology for developing their managers (Dotlich and Noel, 1998;Boshyk, 2002;O'Neil and Marsick, 2007;Boshyk and Dilworth, 2010;Volz-Peacock, Carson and Marquardt, 2016). The focus on learning while working through challenging work problems has also been clearly highlighted in the literature.…”
Section: The Role Of the Action Learning Facilitatormentioning
confidence: 97%
“…More recent research by Volz-Peacock, Carson and Marquardt (2016) highlight that AL provides a safe, social and collaborative environment for developing leaders around the world in public and private sectors.…”
Section: Action Learning In Leadership Developmentmentioning
confidence: 99%
“…Many assertions have been made about the benefits of action learning instructional strategies for teaching and learning across different disciplinary boundaries. Some of these scholars have reported the teaching-learning utilities inherent in action instructional strategies in the fields of leadership development (Volz-Peacock, Carson, & Marquardt, 2016), change and learning in networks, an aspect of applied behavioural science (Coghlan & Coughlan, 2015) and integration of social media in the classroom (Casey & Evans, 2017). Action learning is built on small groups of colleagues meeting over time to solve problems or issues to get things done.…”
Section: Action Learning Instructional Strategymentioning
confidence: 99%
“…Some scholars attribute the improvement in students' learning outcomes to the willingness to share ideas and 'learn in group' opportunities afforded learners by the action learning lenses as against the teacher centered approach operated in conventional lecture method (O'Hara, Bourner, & Weber, 2004;. Evidences from research have shown that action learning has the potentials of developing the three levels of learning namely: leader/individual, team, and organizational (Volz-Peacock, Carson, & Marquardt, 2016). The implication of these strengths of action learning for an educational researcher is that, this instructional strategy can develop the headteacher/ teacher, team of learners, and the school as well.…”
Section: Action Learning Instructional Strategymentioning
confidence: 99%
“…Despite the vital role played by leadership across different spheres of the society, numerous scholars argue that extant leadership development literature is shallow on leadership development theories (Snook et al, 2012;Day, Fleenor, Atwater, Sturm, & Mckee, 2014;Volz-Peacock, Carson & Marquardt, 2016). It is the author's understanding that leadership development is learning what leadership is and how to lead, particularly how to be an ethical and effective leader.…”
Section: Leadership Developmentmentioning
confidence: 99%